Mengaktualisasikan Nilai-nilai Kearifan Lokal dalam Tradisi Marpangir sebagai Sumber Pembelajaran Ilmu Pengetahuan Sosial - Afifah, Fellen; Ponidi, Ponidi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study investigates the values of local wisdom embodied in the Marpangir tradition practiced by the community of Kota Natal as they prepare for the holy month of Ramadan, with a particular focus on its potential integration into Social Studies learning. Rooted in cultural and religious practices, Marpangir serves not only as a ritual of physical and spiritual purification but also as a medium for transmitting values such as cleanliness, piety, solidarity, and communal cooperation. These values are essential in shaping students' character and fostering cultural awareness through contextual learning. Employing a qualitative research approach with ethnographic methods, data were collected through participant observation, in-depth interviews, and document analysis. The findings reveal that the Marpangir tradition represents a rich educational resource that can be meaningfully incorporated into Social Studies curricula to enhance students' understanding of local culture and strengthen their social and moral values. This study concludes that integrating local cultural traditions into educational content not only preserves heritage but also enriches pedagogical practices in multicultural contexts.